Empowering Human Resources through Digitization and IoT Training: Development of Remote Home Lighting Control System Using IoT - Gunawan Gunawan; Sandi Fadilah (Jurnal Pengabdian Masyarakat, 2023)
Purpose: This research paper focuses on the empowerment of teenagers in the Renggong hamlet through the development of a remote home lighting control system using IoT technology. The study addresses the implementation process, teenage responses, and the impact on their quality of life, shedding light on the significance of technology in their daily lives. Method: Employing a qualitative approach, the study conducted surveys during outreach in the Renggong hamlet. The research design involved the development of an IoT-based lighting control system, with data collected through participant responses and engagement. Qualitative analysis techniques were utilized to interpret the findings. Practical Applications: The research demonstrates practical applications of IoT, enhancing teenagers' awareness and skills. Its insights benefit education, technology, and community development programs, facilitating digital empowerment. Conclusion: This study highlights IoT's transformative role, promoting digital literacy and skills among youth. Its findings enrich our understanding of technology's potential, benefiting educational and community initiatives significantly.